Computer incident response and forensics team management conducting a successful incident response - Johnson, Leighton (Syngress, 2014)
This book provides security professionals with a complete handbook of computer incident response from the perspective of forensics team management. This approach demonstrates the concepts and principles needed to conduct a successful incident response investigation, ensuring that proven policies and procedures are established and followed by all team members.